2021
DOI: 10.3390/microorganisms9091997
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Hemolytic Uremic Syndrome Related to Treatment of Escherichia coli O157 Infection with Different Antimicrobial Classes

Abstract: Treatment of Shiga toxin-producing Escherichia coli O157 (O157) diarrhea with antimicrobials might alter the risk of hemolytic uremic syndrome (HUS). However, full characterization of which antimicrobials might affect risk is lacking, particularly among adults. To inform clinical management, we conducted a case-control study of residents of the FoodNet surveillance areas with O157 diarrhea during a 4-year period to assess antimicrobial class-specific associations with HUS among persons with O157 diarrhea. We c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
(66 reference statements)
0
3
0
Order By: Relevance
“…This approach appeared safe, since no HUS-related clinical or laboratory deterioration occurred. In contrast to these findings in asymptomatic long-term carriers, antibiotics are generally discouraged during STEC-related acute bloody diarrhea (12)(13)(14). In vitro, Stx production is boosted by sub-inhibitory concentrations of specific antibiotics.…”
Section: Community Case Series Of Sporadic Asymptomatic Long-term Car...mentioning
confidence: 99%
See 2 more Smart Citations
“…This approach appeared safe, since no HUS-related clinical or laboratory deterioration occurred. In contrast to these findings in asymptomatic long-term carriers, antibiotics are generally discouraged during STEC-related acute bloody diarrhea (12)(13)(14). In vitro, Stx production is boosted by sub-inhibitory concentrations of specific antibiotics.…”
Section: Community Case Series Of Sporadic Asymptomatic Long-term Car...mentioning
confidence: 99%
“…This is plausible, as both antibiotics, targeting DNA-synthesis, induce the bacterial SOS stress response to DNA damage, which is linked to an increase in phage production and toxin release (24)(25)(26). Additionally, a retrospective analysis from the US FoodNet surveillance recently reported an augmented risk of HUS among children and adults with O157 diarrhea treated with β-lactams (14). For other strains, data were conflicting and hardly comparable due to different antibiotics at variable doses and variable susceptibility profiles.…”
Section: Community Case Series Of Sporadic Asymptomatic Long-term Car...mentioning
confidence: 99%
See 1 more Smart Citation
“…In clinical studies, FQs therapy leads to beneficial results, although unfavorable results were reported in in vitro studies. Recently, Mody et al [ 392 ] suggested that the assessed antimicrobial classes for treating O157 diarrhea should be avoided, especially β-lactams, which increased the odds of the hemolytic-uremic syndrome. Targeted classes of antibiotics were β-lactams, FQs, nitroimidazoles (metronidazole), macrolides, and sulfonamides (sulfamethoxazole-trimethoprim).…”
Section: Side-effects Of Fqs and Underlying Mechanismsmentioning
confidence: 99%
“…Additionally, the increased number of fluorine atoms could be responsible, but it is still an unfounded hypothesis [ 100 ]. In patients with Escherichia coli -associated diarrhea treated with antibiotics associated with the hemolytic-uremic syndrome, production and the release of toxic seems to be the primary mechanism [ 392 ].…”
Section: Side-effects Of Fqs and Underlying Mechanismsmentioning
confidence: 99%